The Dialectic of Law and Infringement - Shaw, Wendy M. K (Possessors and Possessed, 2003)
Not only did the museum function as an ideological bridge between European and Ottoman heritage, under Osman Hamdi it also served as a battleground for possession of the physical elements of that heritage. The antiquities legislation of the Ottoman Empire developed as a dialectic negotiation between the writing of the law and a series of subsequent infringements that resulted in more detailed versions in 1884 and 1906. Each successive law not only addressed the deficiencies of its predecessor, it also reflected new values that had become associated with antiquities in the interim. Given the numerous loopholes in the 1874 antiquities